Potassium management and residue recycling effects on wheat (Triticum aestivum) under maize (Zea mays) – wheat rotation - ARORA, KAJAL; BANA, R S; SEPAT, SEEMA (The Indian Journal of Agricultural Sciences, 2022)
The crop residue application and the balanced fertilization with 3 major macronutrients mainly emphasizing on different potassium management practices significantly improve the yield attributing components of wheat crop. Likewise, the highest grain, straw and biological yield in wheat crop was observed with crop residue retention and the split application of 100% RDK (½ at basal + ½ top dress at 25 DAS). The maximum production efficiency and monetary efficiency was recorded under the crop residue retention. Among the potassium management practices the efficiencies were recorded maximum with the split application of 100% RDK (½ at basal + ½ top dress at 25 DAS). Hence, it can be concluded that for enhanced productivity and greater monetary efficiency, the crop residue retention and the split application of 100% RDK (½ at basal + ½ top dress at 25 DAS) could be a better management practice for better growth and development of wheat crop in a maize-wheat rotation. However, to have greater insights on the residue retention and potassium effects, the future research may focus on understanding water and nutrient release pattern in the soil profile, improvement in soil physical and mechanical properties, rhizospheric microbial dynamics and physiological effects on the wheat plants due to diverse residue management systems and potassium application protocols.